Improved water safety planning: insights into the role of organisational culture - Summerill, Corinna (Cranfield University, 2010)
Unsafe water, as many recent outbreaks have shown, has the potential to cause widespread illness and even death. Water Safety Plans (WSPs) are advocated as the best way of ensuring good safe drinking water using a risk management approach. Using a case study approach to generate qualitative data, organisational culture and WSP development in water suppliers of varying size, development and structure was studied to look for examples of best practice or barriers to effective implementation. Despite WSPs being promoted since 2004, suppliers are still experiencing challenges in implementation, with deeper organisational culture barriers prevalent such as: lack of awareness and recognition; uncertainty; complacency; poor internal relationships; competing priorities; and contrasting internal cultures, in addition to the commonly espoused reasons of a lack of time or resources. Concern was raised that the public health motivator of WSPs was becoming lost, as a wide range of additional ‘added value’ drivers and benefits were identified such as cost savings or commercial drivers. This was echoed in broader organisational missions and drivers identified; whilst may employees still identified quality and public health as important, more formal declarations often prioritised other areas. In response to identified organisational culture barriers, a ‘taxonomy’ of positive cultural attributes and a number of practical tools were developed that may assist suppliers in developing a supportive organisational culture for sustainable WSP implementation. These positive elements included: managerial commitment; learning culture; effective internal and external relationships; accountability; open reporting culture; continual improvement culture; empowerment of staff; organisational commitment; proactivity; leadership and advocacy; mindfulness of public health; image and competitiveness. A number of recommendations can be made to those wishing to implement WSPs. Primarily, it is urged that organisational culture and how it can impact on effective WSP implementation should be considered. Perceived lack of time and resources may actually be representative of deeper cultural barriers, and recognise that WSP implementation is more than just following a set of instructions, it will require instilling a water safety ‘culture’ within the organisation.